Children’s Gratitude: Implication of Contextual and Demographic Variables in Argentina - Oros, Laura Beatriz; Schulz-Begle, Annie; Vargas-Rubilar, Jael (Revista Latinoamericana de Ciencias Sociales, Niñez y Juventud, 2015)
This article explores the motives for gratitude expressed by children, taking into account contextual and demographic variables. The sample consisted of 249 participants aged between 8 and 10 years from Argentina, of which 127 were middle SES children (Group 1) and 122 were low SES children (Group 2). The study used a free response technique and Cramér’s V tests were performed to analyze whether the responses were associated with SES, gender and age. The most prominent motive for gratitude in Group 1 was related to having a family. Children from the lower SES group demonstrated gratitude for being able to have material objects and the basic elements necessary for survival, among which food was emphasized. Girls focused their gratitude on loving relationships, whereas boys mentioned material objects, borrowed objects, as well as autonomy granted by their parents. The motives for gratitude were also found to be significantly associated with age.